Design and implementation of mimo-long term evolution-advanced to support larger bandwidth - Alashqer , Aws Zuheer Yonis (2013)
The migration of mobile communication technologies are divided into four generations. Long Term Evolution (LTE) is called LTE rel-8, the evolution of LTE led to new technology referred to as LTE-Advanced, is the true fourth generation (4G) evolution step, with the first release of LTE (rel-8) which was labeled as “3.9G”. LTE-Advanced is a mobile broadband access technology founded as a response to the need for the improvement to support the increasing demand for high data rates. The standard for LTE-A is a milestone in the development of Third Generation Partnership Project (3GPP) technologies. Carrier Aggregation is one of the most distinct features of LTE-Advanced that makes the bandwidth extension of up to 100 MHz thus the theoretical peak data rate of LTE-A may be even up to 1 Gbps. This proposed system presents new LTE-Advanced depending on carrier aggregation to obtain better performance of the system. The new design of LTE-Advanced offers higher peak data rates than even the initial LTE-A; while the spectrum efficiency has been amended; As a result, the aggregated LTE-A will support 120 MHz instead of 100 MHz in order to obtain higher peak data rate access up to 4 Gbps. The system was applied with 8x8 Multiple Input Multiple Output (MIMO) using different modulation techniques: QPSK, 16 QAM, and 64 QAM. From the simulation results, it is clear that proposed LTE-Advanced with 64 QAM has high values of throughput in case of depending code rate equals to 5/6 with 8x8 MIMO.